206 Impact of the birth month in the development of systemic lupus erythematosus. (April 2019) - Frittoli, Renan; Marini, Roberto; Costallat, Lilian; Appenzeller, Simone
Abstract : Background: There is evidence that most individuals with Systemic Lupus Erythematosus (SLE) have been born at the end of the winter season, mainly because of the influence of the mother's exposure to sunlight during pregnancy, possibly affecting vitamin D metabolism. The objective was to evaluate the influence of the birth month in the development of SLE. Methods: We included consecutive patients with childhood-onset SLE (cSLE) (age at onset of disease 16 years) and adult-onset SLE (age of onset of disease >16 years) from the Rheumatology outpatient unit in Brazil. The control group consisted of volunteers no history of autoimmune disease. Through the review of medical records the patient's date of birth was obtained and the patients were classified according to the months and seasons of the year in which they were born. The results were presented in a descriptive way and the statistical analysis was performed through the chi-square test. For all analyzes p<0.05 was considered statistically significant. Results: A total of 1460 subjects (760 patients and 700 controls) were included. Of the patients analyzed, 662 (87.1%) were adult-onset SLE and 98 cSLE (12.89%). The mean age of the adult SLE was 42.4 years (SD ±12.7) and cSLE was 17.8 years (SD ±4.4). The controls had a mean age of 24.5 years (SD ±10.1). Patients who were born at the end of the winter season [n=65 (8.5%)] presented a statistically significant difference in relation to the control group [n=55 (7.8%)] (p=0.011). When it was considered only patients with cSLE, it was observed a significantly higher birth numbers of cSLE patients during the winter season in Brazil (June 21-September 21) when compared to the controls (p=0.018), and cSLE presented presented a birth frequency in winter (35.7%) twice as high as those born in summer (17.34%) and spring (17.34%). A significant difference was also observed in cSLE in the month of August (which is winter in Brazil) (p=0.042), when compared to the controls. Adult SLE had no differences with the control group in any month (p>0.05). Conclusions: It is believed that the winter season interferes with the development of SLE, especially in cSLE. These results may reinforce the idea that climate can be a contributing factor to the development of cSLE. Funding Source(s): CNPq FAPESP